Orações subordinadas adverbiais causais x orações coordenadas explicativas: uma análise empírico-experimental - Consuelo Hermine Santos (2018)
Our research is intended to investigate issues related to the distinction between causal subordinate clauses and independent clauses aiming to help students from Elementary, Middle and High school, understand such a complex issue. The elaboration of this research came from the literary revision of grammarians, linguists and philosophers. We therefore look forward to present the formulated concept to each clause in order to verify wether such concepts are sufficiently clarifying to allow the correct identification of these clauses. We start from the hypothesis that the inversion of the canonical order, is correct, while in the explanatory, it is not. We use as methodology, within the experimental syntax, based on the criterion of acceptability. The result of the experiment revealed that both the inversion of the causal and the inversion of explicative were well accepted by participants, but it suggested that semantic factors related to the entailment between the clauses of the period differentiate the causal clauses from the explicative ones once they denote an efficient cause and those, a real cause.